The mealtime experience of family carers of people with Motor Neurone Disease (MND)-related feeding and swallowing disabilities: A grounded theory study - Daly, Stacey (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2024)
Family members of people with MND (PwMND) are impacted in profound ways by the presence of this illness and the numerous disabilities that can arise, including feeding and swallowing disability. Provision of assistance with eating, drinking and mealtime functioning has been identified as one of the most significant roles of family carers, requiring considerable physical and emotional resource. To date, a limited number of studies have investigated the impact of eating, drinking and mealtime changes on family carers of PwMND and these studies have primarily focused on the experience of specific interventions (e.g., gastrostomy) for swallowing disability. Further information is required to inform understanding of family carer perspective and enhance family-centred care. This study sought to develop an in-depth understanding of the mealtime experience for family carers of PwMND. Grounded theory methodology was used to address the study aim, which included the generation of a conceptual framework accounting for family carer experience. Twenty-one family carers were sampled across Ireland in this study. Participants were recruited via the Trinity College Dublin-based Research Motor Neurone group, the National Centre of ALS/MND at Beaumont Hospital (Dublin), and the Irish Motor Neurone Disease Association. In-depth, semi-structured interviews were conducted with participants regarding their experience of MND-associated feeding, swallowing and mealtime changes. In keeping with the methodology, lines of questioning evolved over the data set in response to theoretical leads arising through the concurrent processes of data collection and analysis. Data analysis involved open, axial, and selective coding of interview transcriptions. Theoretical memoing and concept diagramming were also used to develop a conceptual framework. The conceptual framework constituting the findings for this study outlines a transformed psycho-emotional landscape for family carers both underpinning and influenced by family carer experience of feeding, swallowing and mealtime difficulties. Unique feeding, swallowing and mealtime-related demands, situations, and experiences contributing to the psycho-emotional context of carers were identified. In this study, negative psycho-emotional sequalae required bearing, braving and persevering due to unpredictability, uncertainty, and the family carer's inability to control both the presence and progression of the illness, and feeding, swallowing and mealtime-related consequences. Actions of health and social care professionals (HSCPs) were uncovered as both facilitators and barriers in multiple aspects of the family carer's experience of feeding and swallowing disability. The categories identified within the psycho-emotional context of the framework included sadness and loss, fearfulness, anger and frustration, guilt and regret, and hope. In order to cope with and adapt to the presence of feeding, swallowing and mealtime challenges, family carers sought to remain present in the moment. Family carer hope was identified as central to the ability to bear, brave and persevere with family caring in the context of MND-related feeding, swallowing and mealtime changes. This study identified that the actions and interactions of family carers in the context of feeding and swallowing disability were fundamentally underpinned by their desire to protect and as such protection represents the core category within the conceptual framework. Family carers enacted protection of the care-recipient, the wider family unit and, under specific circumstances, themselves when faced with feeding, swallowing and mealtime challenges. Family carer protection was orientated towards the physical, psycho-emotional and/or psycho-social domains of functioning and family carer prioritisation of protection was influenced by multiple care-recipient, family unit and family carer-related factors as identified in this study. Several strategies were used by family carers to operationalise protection when supporting care recipients to navigate feeding, swallowing and mealtime challenges. Problem solving, balance and compromise, gatekeeping, strategic communication, change management and teamwork and leadership were key actions and interactions uncovered, as represented within the conceptual framework. The nature and quality of the relationship between the care-recipient and the family carer pre-dating the illness was identified as integral to the family carer's ability to navigate role and relationship changes which were unavoidable with the establishment of a care relationship. The findings of this study illustrate the depth of the role of family carers in supporting eating, drinking and mealtime difficulties experienced by PwMND. The significance of family carer contribution in optimising the health and wellbeing of PwMND and the extent of the compromises family carers make in providing home-based care are explained. This study highlights the sensitivity required of HSCPs who work with family carers in the context of MND-induced feeding, swallowing and mealtime-related changes. The knowledge arising from this study may be used to inform future research aimed at better understanding third-party feeding and swallowing disability and may improve the quality of dysphagia care provided to families impacted by MND.
APPROVED
Keywords: Grounded theory; Family caregiving; Motor Neurone Disease; Swallowing; Dysphagia; Mealtime; Third-party disability; Feeding dependence